The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1111/j.1365-2338.1996.tb01543.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary account of the phytosanitary status of stone‐fruit trees in Lebanon

Abstract: Investigations were carried out in the main stone‐fruit growing areas of Lebanon to assess the phytosanitary condition of commercial orchards. The presence of virus and virus‐like diseases and their identification was ascertained through: (i) field surveys, (ii) sap transmission to herbaceous hosts, (iii) graft transmission to woody indicators; and (iv) ELISA and IEM tests. The mean infection level was 25%. ranging from 5% in apricot to 45% in cherry. The following viruses were identified: apple chlorotic leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
(4 reference statements)
0
9
0
Order By: Relevance
“…Differenial transmission of individual viruses through rootstocks and, perhaps, pollen may account for these differences (Digiaro & Savino, 1992). ApMV, which was no1 detected in a previous survey (Jawhar et al, 1996), is reported for the first time in peach in Lebanon. The low incicence of ApMV in the country is remarkable, especially as this virus is not rare in the Mediterranean region (Savino e* al., 1995).…”
Section: As Shown Inmentioning
confidence: 75%
See 1 more Smart Citation
“…Differenial transmission of individual viruses through rootstocks and, perhaps, pollen may account for these differences (Digiaro & Savino, 1992). ApMV, which was no1 detected in a previous survey (Jawhar et al, 1996), is reported for the first time in peach in Lebanon. The low incicence of ApMV in the country is remarkable, especially as this virus is not rare in the Mediterranean region (Savino e* al., 1995).…”
Section: As Shown Inmentioning
confidence: 75%
“…2), PLMVd was detected in 17 samples belonging to native and imported varieties (Babcock, Chikhani, Springtime, Nectarose, Dixiered) grown in all areas surveyed. (Jawhar et al, 1996). ACLSV was second in pxevalence, occurring in 27.1% of the surveyed orchards, followed by PDV (22.4%) and ApMV (2.1 %).…”
Section: As Shown Inmentioning
confidence: 96%
“…It is comparable with that recorded from neighbouring countries, i.e. Jordan (Al‐Rwahnih et al ., 2001), Lebanon (Jawhar et al ., 1996) and Palestine (Jarrar et al ., 2001). PPV was reported earlier in Syria (Dunez, 1986), but it seems that the eradication of the infected trees carried out by local institutions was effective in controlling the disease.…”
Section: Discussionmentioning
confidence: 99%
“…ACLSV has been reported from sweet cherry ( P runus avium ) from China (Z hou et al. 1996), Turkey (S ipahioglu and B aloglu 2006), Lebanon (J awhar et al. 1996), Syria (I smaeil et al.…”
Section: Percent Identities Nucleotide (Above Diagonal) and Amino Acmentioning
confidence: 99%
“…Apple chlorotic leaf spot virus, a type species of the genus Trichovirus (Martelli et al 1994), frequently causes symptomless infections but can induce severe graft incompatibilities in some Prunus combinations, causing major problems in nurseries (Ulubas and Ertunc 2005). ACLSV has been reported from sweet cherry (P runus avium) from China (Zhou et al 1996), Turkey (Sipahioglu and Baloglu 2006), Lebanon (Jawhar et al 1996), Syria (Ismaeil et al 2002), Italy (Grayaa et al 1993) and Japan (Isogai et al 2004). Myrta (1998) reported 40% infection of ACLSV in sweet cherry from Albania.…”
mentioning
confidence: 99%